Implications of Constitutional Court Decision number 83/PUU-XXII/2024 on Procedures and Proof of Police Claims in Life Insurance Disputes - Reza Yuda; Kamal Ubaidillah (Law Research Review Quarterly, 2026)
Life insurance disputes in Indonesia frequently reveal a significant power imbalance between policyholders and insurance companies, traditionally exacerbated by Article 251 of the Commercial Code (KUHDagang) that allowed unilateral policy cancellations by insurers. This research aims to comprehensively examine the implications of the Constitutional Court Decision No. 83/PUU-XXII/2024 on the procedures and evidentiary requirements of policy claims in life insurance disputes. The study adopts a normative juridical approach, utilizing qualitative descriptive-analytical methods to evaluate legal documents, norms, and principles. The findings indicate a paradigm shift from an insurer-centric process to a balanced mutual legal framework. The Constitutional Court decision eliminates the insurer's right to unilaterally cancel policies based on misrepresentation, now mandating mutual agreement or a binding court decision. Consequently, the burden of proof is rebalanced, compelling insurers to conduct rigorous pre-event underwriting and prove material misrepresentation during dispute resolution. In conclusion, the ruling fundamentally restores policyholders' constitutional rights and legal certainty. However, to fully realize these equitable procedural shifts, regulatory bodies and the industry must implement operational harmonizations, including revising standard policy clauses, establishing clear material evidence guidelines, and strengthening non-litigation mediation mechanisms.